The annotated list of Cyanoprocaryota marine rocky supralittoral Natural Reserves "Cape Martian" (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The list of 78 Cyanoprokaryota species in supralittoral zone of the natural reserve has been geven in the article. The greatest number of species are of the familys Oscillatoriaceae – 17 species and Rivulariaceae – 14 species. Among the genera Lyngbya C. Agardh ex Gomont, submitted with nine species is dominant. Genera Calothrix C. Agardh ex Bornet et Flahault and Plectonema Thur. ex Gomont have 6 and 5 species respectively, 6 genera are represented by three and four species, two genera – by two species, the rest 12 genera have only one species in each. Generally in the nature reserve there are 27 (34,2%) of brackish water, 23 (29,1%) aerofitic, 18 (22,8%) evribiontov, 7 (8,9%) epiphytic and 4 (5,1%) freshwater species. The overwhelming majority of species are cosmopolitan (57,0%), a large part is temperate zone species – 38,0% and only 5,0% of the species have been recorded in the subtropical zone.
Keywords: Cyanoprocaryota, nature reserve